Generation and Characterization of a Human/Mouse Chimeric GD2-Mimicking Anti-Idiotype Antibody Ganglidiximab for Active Immunotherapy against Neuroblastoma. - Christin Eger; Nikolai Siebert; Diana Seidel; Maxi Zumpe; Madlen Jüttner; Sven Brandt; Hans-Peter Müller; Holger N Lode (PLoS ONE)
Vaccination with proteins mimicking GD2 that is highly expressed on neuroblastoma (NB) cells is a promising strategy in treatment of NB, a pediatric malignancy with poor prognosis. We previously showed efficacy of ganglidiomab in vivo, a murine anti-idiotype (anti-Id) IgG1. In order to tailor immune responses to variable regions, we generated a new human/mouse chimeric anti-Id antibody (Ab) ganglidiximab by replacing murine constant fragments with corresponding human IgG1 regions. DNA sequences encoding for variable regions of heavy (VH) and light chains (VL) were synthesized by RT-PCR from total RNA of ganglidiomab-producing hybridoma cells and further ligated into mammalian expression plasmids with coding sequences for constant regions of human IgG1 heavy and light chains, respectively. We established a stable production cell line using Chinese hamster ovarian (CHO) cells co-transfected with two expression plasmids driving the expression of either ganglidiximab heavy or light chain. After purification from supernatants, anti-idiotypic characteristics of ganglidiximab were demonstrated. Binding of ganglidiximab to anti-GD2 Abs of the 14.18 family as well as to NK-92tr cells expressing a GD2-specific chimeric antigen receptor (scFv(ch14.18)-zeta) was shown using standard ELISA and flow cytometry analysis, respectively. Ganglidiximab binding affinities to anti-GD2 Abs were further determined by surface plasmon resonance technique. Moreover, binding of anti-GD2 Abs to the nominal antigen GD2 as well as GD2-specific Ab-mediated cytotoxicity (ADCC, CDC) was competitively inhibited by ganglidiximab. Finally, ganglidiximab was successfully used as a protein vaccine in vivo to induce a GD2-specific humoral immune response. In summary, we report generation and characterization of a new human/mouse chimeric anti-Id Ab ganglidiximab for active immunotherapy against NB. This Ab may be useful to tailor immune responses to the paratope regions mimicking GD2 overexpressed in NB.